The crossroad between autoimmune disorder, tissue remodeling and cancer of the thyroid: The long pentraxin 3 (PTX3) - Chiari, Damiano; Pirali, Barbara; Perano, Vittoria; Leone, Roberto; Mantovani, Alberto; Bottazzi, Barbara (Frontiers in Endocrinology, 2023)
Thyroid is at the crossroads of immune dysregulation, tissue remodeling and oncogenesis. Autoimmune disorders, nodular disease and cancer of the thyroid affect a large amount of general population, mainly women. We wondered if there could be a common factor behind three processes (immune dysregulation, tissue remodeling and oncogenesis) that frequently affect, sometimes coexisting, the thyroid gland. The long pentraxin 3 (PTX3) is an essential component of the humoral arm of the innate immune system acting as soluble pattern recognition molecule. The protein is found expressed in a variety of cell types during tissue injury and stress. In addition, PTX3 is produced by neutrophils during maturation in the bone-marrow and is stored in lactoferrin-granules. PTX3 is a regulator of the complement cascade and orchestrates tissue remodeling and repair. Preclinical data and studies in human tumors indicate that PTX3 can act both as an extrinsic oncosuppressor by modulating complement-dependent tumor-promoting inflammation, or as a tumor-promoter molecule, regulating cell invasion and proliferation and epithelial to mesenchymal transition, thus suggesting that this molecule may have different functions on carcinogenesis. The involvement of PTX3 in the regulation of immune responses, tissue remodeling and oncosuppressive processes led us to explore its potential role in the development of thyroid disorders. In this review, we aimed to highlight what is known, at the state of the art, regarding the connection between the long pentraxin 3 and the main thyroid diseases i.e., nodular thyroid disease, thyroid cancer and autoimmune thyroid disorders.